Significados das mensagens publicadas no mural do Facebook: uma análise temática - Keiserman, Boris Brancaglion (2012)
The use of social networking sites on the internet is a phenomenon of growing importance in our everyday life. With over 37 million users in Brazil and 1 billion worldwide, Facebook is today the most popular social networking site in the West. A great number of books and magazine articles have dedicated their pages to Facebook, how it has changed our lives and how some lives have become it´s hostage. This dissertation is an attempt to understand the significance of Facebook to its users, aiming to comprehend what is written, how it´s written and why information is published on Facebook. It is an exploratory study, which has as an objective to analyze information posted on the Facebook Wall by participants of a social network trying to understand the different types of interactions which occur between the network´s users. A qualitative analysis was conducted referring to 72 hours of wall activity on a Facebook user´s all and then the category which was targeted as the one generating the greater number of responses was qualitatively analyzed. We have concluded that publications with personal reports are of extreme importance in maintaining Facebook activity, disclosing emotional content which aid in maintaining the user´s offline social network active. It is a way of maintaining a support network in an easy and efficient fashion